Design of Selectable Modems for MC-CDMA Based on Software Defined Radio - Nahar, Ali Kareem; Yusnita, Rahayu (Penerbit Universiti Malaysia Pahang, 2015)
MC-CDMA technique is the combination of Orthogonal Frequency Division Multiplexing (OFDM) technique and Code Division Multiple Access (CDMA) technique and collects the benefit of both techniques to provide higher data rates and greater flexibility for voice, data, video and internet services for future wireless systems. In this paper MC-CDMA system based on Software Defined Radio (SDR)was proposed. The proposed data spread model consist of gold code and Selectable six modulation types (BPSK, QPSK, 8QAM, 16QAM, 32QAM and 64QAM)